Electroadsorption of La3+ and Ce3+ from Aqueous Media with a Carbon Paste Electrode Modified with Hms-Cmpo - Pizarro-Konczak, J; Matta-Palacios, A; Gómez-Barrena, M; Diaz-Navarro, C (Elsevier B.V., 2024)
This work deals with the electroadsorption of rare earths cerium and lanthanum in aqueous solution by using a carbon paste electrode modified with a silica mesoporous material functionalized with carbamoyl methyl phosphine oxide (CMPO). This functionalization was carried out in a two-step synthesis, the intermediate product was synthesized by attaching N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (APTMS) to the surface of the HMS by a grafting method synthesis, then this intermediate was modified by CMPO, in a further condensation reaction. The final product CMPO obtained was characterized by diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), thermal gravimetric analysis (TGA) and N2 adsorption/desorption isotherms using BJH and BET models. Showing thermal stability, a surface area higher than 450m2g-1 and mesoporous properties. The CMPO material was used to modify the mixture of the carbon paste electrode producing an enhancement in the interaction between the electrode surface and the lanthanides studied, at the same time it produces and improvement in the electroactive area by over two orders of magnitude. The modified carbon paste electrode (CMPO-CPE) developed in this work shows an increase in the conductivity, observed with the electrochemical impedance spectroscopy studies, and an increase in the electroactive area of 47 % was calculated from cyclic voltammetry experiments. CMPO-CPE was used to extract La3+ and Ce3+ from aqueous solution using NaNO3 as support electrolyte, by using a fixed potential program over time, measuring the obtained current by Chronoamperometric method. The adsorption and desorption results were corroborated with Inductively coupled plasma atomic emission spectroscopy (ICP-OES) demonstrated the capacity of extraction of the electrode were 74 μg after ten cycles for La3+ at pH 5.0 and 15 μg after ten cycles for Ce3+ at pH 6.0, using a CMPO modified electrode of small surface (3 mm radius). This electrode was tested for over 50 cycles without losing their electroactive properties under tested electrochemical conditions. © 2024